An Assessment of the Role of Mothers’ Union in the Children’s Ministry: A case Study of Kasindaga Deanery, Lweru Diocese, Anglican Church of Tanzania - Innocensia Bijobwa (My University, 2023)
This study discussed the role of Mothers’ Union in the Children’s ministry in Kasindaga Deanery, Diocese of Lweru, Tanzania. The objectives of the study were: to examine how Mothers’ Union Members engage in the children's ministry activities in Kasindaga Deanery, Diocese of Lweru, to examine the reasons why sometimes Mothers’ Union members fail to fulfill their roles in the children’s ministry in Kasindaga Deanery, Diocese of Lweru and to come up with recommendations to ensure that the Mothers’ Union objective of effective children’s ministry is achieved in Kasindaga Deanery, Diocese of Lweru. A cross-sectional study design using a sample of 50 respondents was adopted. Findings revealed that 76% of the respondents said that the Church prays for the children through the Mothers’ Union members. It was also established that 46% of the respondents said that Mothers’ Union members sometimes fail to fulfill their roles in the children’s ministry due to the drought which causes a shortage of food. In addition, 66% of the respondents said that the Church should strengthen the good teachings of the Bible about the children and teach good faith by example to ensure that the Mothers’ Union objective of effective children’s ministry is achieved in Kasindaga Deanery, Diocese of Lweru. The study recommends that Mothers’ Union must get training on how to lead children in a Godly way. Mothers’ Union in Kasindaga Deanery, Diocese of Lweru need to develop the church membership and begin discipleship classes for children. In addition, there should be a mass sensitization about the need for effective children’s ministry in Kasindaga Deanery, Diocese of Lweru so that the members of Mothers’ Union and congregants can actively participate in children’s ministry.
This is a dissertation.